Quality of Service (QoS) Vsat Ip On The Network Wide Area Network (WAN) - Sari Dewi; Hanggoro Aji Al Kautsar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Satellite media is an alternative communication technology that can be applied to meet the communication needs of regions with geographical conditions in the archipelago. One technology that uses a satellite communication system is an automated teller machine (ATM) which is observed in this study. In this case, all observed ATMs use a Very Small Apperture Terminal (VSAT) antenna as a communication system between ATMs and bank servers. One of the most common problems is transactional failure in which the network communication system does not connect to the server from the ATM. Therefore, standardization of signal quality factor (SQF) is applied to maintain network quality. The survey method used is the observation method by observing the analysis of service quality. Several parameters used to determine the quality of the VSAT IP network include delay, data rate, and quality of service level of the VSAT IP communication system in the company. Second, optimization of network quality. This requires remote migration from VSAT to a new and more stable hub.